Association of maternal dietary patterns in early pregnancy with gestational weight gain: Yazd Birth Cohort - Shahab-Aldin Akbarian; Amin Salehi-Abargouei; Sara Jambarsang; Habib Nikukar; Azadeh Nadjarzadeh (International Journal of Reproductive BioMedicine)
Background: Abnormal gestational weight gain (GWG) can carry risks for both the mother and the baby. Diet imbalances are the determining factor in the weight gain of pregnant women.